DIAGNOSIS OF THE USE OF AGRICULTURAL TRACTORS IN THE STATE OF RORAIMA - da Silva, Edgley Soares; da Cruz, Matheus Willians Sousa; Monteiro Neto, João Luiz Lopes; Cruz, Ana Bárbara de Souza; Gonçalves, Anderson Carlos de Melo; Reyes, Veronica Nathaly Arevalo (Seven Editora, 2026)
The accelerated growth in the use of agricultural mechanization in Roraima brought up recurring problems in other regions of the country, such as the lack of qualified labor for the operation, the lack of technical and mechanical assistance, the lack of parts and difficulty in replacing them. Therefore, the aim of this study was to carry out a diagnosis of the use of agricultural tractors in the State of Roraima, with emphasis on identifying the main problems related to breakage, with a view to replacing parts. The survey was carried out between March and October 2022 and included interviews with 32 local rural producers, who answered a questionnaire containing 09 questions related to the topic. It was concluded that most producers looking for assistance for their tractors are from the municipalities of Cantá, Alto Alegre and Boa Vista. The activities carried out in the State of Roraima that most use agricultural mechanization are livestock, soy and corn cultivation. Most producers in Roraima have only one tractor. The largest number of tractors is in the municipality of Alto Alegre, as well as the producers who have the largest number of tractors. The most used tractor brands in Roraima are John Deere, New Holland and Valmet/Valtra. Most properties do not have certified operators, however, the main cause of breakage is reported as natural wear and tear. Most of the times when there is a breakdown of tractors, it is possible to find the part for repair in the State itself.